Workshop Plank Exercise untuk Pembelajaran Kebugaran Jasmani bagi Guru PJOK Mi Se-Kecamatan Trowulan - Priadana, Benny; Saifuddin, Hasan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Getting used to regular and regular physical activity is very important to be instilled from an early age to improve children's physical fitness and immunity. However, the problem of the COVID-19 pandemic has made online Physical Education, Sports and Health learning less effective in making children happy to do physical activity on a regular basis. The purpose of this activity is to improve the knowledge and skills of physical education teachers in utilizing plank training activities as physical fitness learning activities effectively and efficiently in this era of the covid-19 pandemic. The method of this activity is a workshop with plank exercise material, as well as assistance on how to apply it at school. The results of this activity showed that the enthusiasm of the participants in participating in the workshop was very good, many expressed that this activity had added new insights for them and was very interesting to apply in schools. The participants' knowledge and skills regarding plank exercises were also very good, this was evident from the high enthusiasm, motivation, and confidence of the participants in applying them to students.